Effect of gut microbiota from Henoch-Schönlein Purpura patients on acid-sensitive ion channel 3 expression and intestinal motility in germ-free rats - Jin-kun Wang; Bo Yan; Jun-mei Zhao; Li-ping Yuan (BMC, 2021)
Abstract Background It has been proven that gut microbiota alterations are involved in the development of Henoch-Schönlein Purpura (HSP). However, the pathogenesis of HSP hasn't been eluciated. This study was to investigate the impact of gut microbiota from HSP on ASIC3 expression and interactions between microbiota and ASIC3 expression in the development of HSP. Methods Feces collected from HSP and healthy children at the First Affiliated Hospital of Anhui Medical University were made into fecal microbial solutions. Germ-free rats were randomly assigned to either the control or HSP groups. The HSP group of rats were administered the fecal microbiota solution of HSP children, while the control group rats were administered the fecal microbiota solution of healthy children. Abdominal withdrawal reflex (AWR) and intestinal propulsion rate of the rats were used to determine visceral sensitivity. Composition of the gut microbiota of HSP children was determined using 16S rRNA gene sequencing. ASIC3 expression in the colon was ascertained through qRT-PCR as well as western blotting analysis. Results The results showed a reduction in the number of species and abundance in the intestinal microbiota of children with HSP. Visceral sensitivity and intestinal propulsion rate of HSP group rats increased significantly, compared with the control group. Colon ASIC3 mRNA and protein levels in the HSP group were found to be upregulated. The microbiota dysbiosis of HSP patients could stimulate ASIC3 expression in the colon of Germ-free rats, which in turn affected intestinal motility. Conclusions These results suggested that HSP children had intestinal microbiota disorder, which might affect gut motility by down-regulating colon ASIC3 expression in rats.